LEGAL CONSTRUCTIONS USED IN CROWDFUNDING - Stanik, M (Człowiek w cyberprzestrzeni, 2020)
The aim of the article is to present the essence of crowdfunding, its basic types and to indicate the basic provisions of Polish law that may be used in running crowdfunding campaigns. The article discusses, among others differences between crowdfunding and public collection, as well as legal acts of Polish law that may apply to specific types of community collections. The conclusion argued for the need to comprehensively regulate the issues analyzed at the level of EU and national legislator.